Method for photocatalytic degradation of perfluorooctanoic acid in water by using boron-group hydroxides

By using boron group hydroxide as photocatalysts, the preparation process is simplified and the photocatalytic degradation reaction is carried out under the light source, and the problems of complex preparation and high cost in existing photocatalysts are solved, achieving efficient and low-cost PFOA degradation effect.

CN119822448AActive Publication Date: 2025-04-15NANJING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510108304.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-15
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

When degrading perfluorooctanoic acid (PFOA), existing photocatalysts have defects such as complex catalyst preparation process, high synthesis cost and strict reaction conditions, which limit their practical application in environmental technology.

Method used

The preparation process is simplified by alkali deposition method by using boron group hydroxide (such as aluminum hydroxide, gallium hydroxide or indium hydroxide) under the light source.

Benefits of technology

It achieves efficient degradation of PFOA in a wide pH range, with a 33.6% improvement in degradation efficiency, while simplifying the catalyst synthesis process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822448A_ABST
    Figure CN119822448A_ABST
Patent Text Reader

Abstract

The invention discloses a method for photocatalytic degradation of perfluorooctanoic acid in water by using boron-group hydroxides, and belongs to the field of sewage treatment. The method for degrading the perfluorooctanoic acid in the water comprises the following steps: adding a boron hydroxide as a photocatalyst into a water body containing the perfluorooctanoic acid, fully mixing, and then carrying out photocatalytic degradation reaction under a light source, the used light source is ultraviolet light, yellow light or red light, and the pH range of the water body containing the perfluorooctanoic acid is 3-7. The perfluorooctanoic acid is subjected to photocatalytic degradation by adopting a series of boron hydroxides (Al (OH) 3, Ga (OH) 3 and In (OH) 3) which are low in cost and simple in preparation process, so that on one hand, the degradation efficiency of the perfluorooctanoic acid in water can be improved, on the other hand, the photocatalytic degradation can be carried out in different light sources and a relatively wide pH range, the application range of photocatalysis is expanded, and the application prospect is wide. The treatment of the PFOA polluted water body in actual production is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage degradation, and in particular to a method for photocatalytically degrading perfluorooctanoic acid in water using boron hydroxides. Background Art

[0002] Perfluorooctanoic acid (PFOA) is defined as a "persistent organic pollutant" due to its strong persistence, bioaccumulation and toxicity. It has been classified as a Class 1 carcinogen, and its transformation and removal in the environment have attracted much attention. Therefore, it is necessary to explore efficient and low-cost degradation methods to improve the degradation efficiency of PFOA.

[0003] At present, various types of photocatalysts have been used in the degradation process of PFOA, mainly focusing on semiconductor photocatalysts such as titanium dioxide, gallium oxide and indium oxide. Among them, the photocatalytic reaction system with boron metal oxides (indium oxide and gallium oxide) as catalysts can effectively degrade PFOA under relatively mild conditions. However, the current photocatalysts still have defects such as complex catalyst preparation process, high synthesis cost, and harsh reaction conditions, which limit their practical application in environmental technology. Therefore, it is necessary to explore other efficient and low-cost catalysts. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for photocatalytic degradation of perfluorooctanoic acid in water using boron hydroxides with a simple synthesis process and high degradation efficiency.

[0005] Technical solution: The present invention discloses a method for photocatalytically degrading perfluorooctanoic acid in water using boron hydroxides, the steps of which are: adding boron hydroxides as photocatalysts to water containing perfluorooctanoic acid, fully mixing, and then performing photocatalytic degradation reaction under a light source.

[0006] Furthermore, the boron hydroxide is aluminum hydroxide, gallium hydroxide or indium hydroxide, preferably aluminum hydroxide.

[0007] Furthermore, the mass ratio of perfluorooctanoic acid to aluminum hydroxide is 1:8-12, preferably 1:10.6.

[0008] Furthermore, the mass ratio of perfluorooctanoic acid to gallium hydroxide is 1:300-600, preferably 1:400.

[0009] Furthermore, the mass ratio of perfluorooctanoic acid to indium hydroxide is 1:40-60, preferably 1:56.

[0010] Furthermore, the preparation method of the boron hydroxide adopts an alkali precipitation method, and the steps are: adding a first concentration of sodium hydroxide solution dropwise to a solution containing aluminum salt, gallium salt or indium salt to generate a white flocculent precipitate, then adding a second concentration of sodium hydroxide solution, and after the precipitate is completely generated, washing the precipitate with a solvent, drying it, cooling and grinding the obtained solid, and the obtained solid powder is a boron hydroxide.

[0011] Furthermore, the concentration of the first concentration sodium hydroxide solution is 8-10M, which is used to generate a certain amount of flocculent precipitate, and the concentration of the second concentration sodium hydroxide solution is 1-2M, which is used to control the particle size of the generated Al(OH)3 or Ga(OH)3 or In(OH)3 to be too large and prevent pH jump.

[0012] Furthermore, the aluminum salt, gallium salt or indium salt is aluminum nitrate nonahydrate (Al(NO3)3·9H2O) or gallium nitrate x-hydrate (Ga(NO3)3·xH2O) or indium nitrate x-hydrate (In(NO3)3·xH2O).

[0013] Furthermore, before the photocatalytic degradation reaction, pre-mixing is required, that is, the solid powder of the boron hydroxide is mixed with the water containing perfluorooctanoic acid and stirred in the dark for 2.0-4.0 hours, the purpose of which is to allow PFOA to be fully adsorbed on the surface of the solid powder of the boron hydroxide.

[0014] Furthermore, the pH range of the water containing perfluorooctanoic acid is 3-7, preferably 7.

[0015] Furthermore, the acid used to adjust the pH of the water containing perfluorooctanoic acid is hydrochloric acid, and the alkali is sodium hydroxide.

[0016] Furthermore, the light source is ultraviolet light, yellow light or red light.

[0017] Furthermore, the conditions of the degradation reaction are: reacting at 24-26°C for 24-50h.

[0018] Furthermore, the concentration range of PFOA in the water body is 1.0 mg / L-100.0 mg / L.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The series of boron hydroxides (Al(OH)3, Ga(OH)3 and In(OH)3) used in the present invention have efficient photocatalytic degradation of perfluorooctanoic acid, and can perform photodegradation under different light sources and photocatalysis in a wider pH range, which greatly broadens the application scope of degradation of perfluorooctanoic acid and is beneficial to the treatment of PFOA-contaminated water bodies in actual production; (2) The present invention prepares boron hydroxides based on the alkali precipitation method, and the synthesis process is simple and time-saving; (3) It has been verified by experiments that after 48 hours of UV irradiation, the degradation efficiency of PFOA can be increased by up to 33.6%. After irradiation with yellow light or red light (LED lamp), the reaction efficiency of the Al(OH)3 or Ga(OH)3 or In(OH)3 photocatalytic PFOA system can be increased by up to 23.5% compared with the single PFOA photolysis system. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Transmission electron microscopy images and X-ray diffraction images of Al(OH)3, Ga(OH)3 or In(OH)3 prepared in Example 1, (a)-(c) are transmission electron microscopy images, and (d)-(e) are X-ray diffraction images;

[0021] Figure 2 This is a diagram of the self-made photoreaction device in Example 4;

[0022] Figure 3 The degradation performance diagram of PFOA by boron hydroxide under a 300W mercury lamp in Examples 1 to 3;

[0023] Figure 4 The degradation performance diagram of boron hydroxide to PFOA in Examples 4 to 6 under yellow light and in Examples 7 to 9 under red light;

[0024] Figure 5 is the utilization efficiency diagram of boron hydroxide;

[0025] Figure 6 Schematic diagram of the degradation of PFOA and the photocatalytic mechanism of boron hydroxides;

[0026] Figure 7 Zeta potential diagrams of three boron hydroxides at different pH;

[0027] Figure 8 FT-IR spectra of boron hydroxide, PFOA and the corresponding adsorption samples;

[0028] Fig. 9 for 19 F NMR optical imaging;

[0029] Fig.10The UV-visible diffuse reflectance absorption spectra of three boron hydroxides are shown in Figure 2.

[0030] Fig.11 (a)-(c) are the emission spectra of three boron hydroxides under variable power excitation at 650nm, and (d)-(f) are the fitting diagrams of luminescence intensity and excitation power. DETAILED DESCRIPTION

[0031] The present invention is further described below in conjunction with specific embodiments and drawings.

[0032] Example 1: The method for photocatalytic degradation of perfluorooctanoic acid in water using boron hydroxide provided in this example comprises the following steps:

[0033] (1) Preparation of photocatalysts - boron hydroxides Al(OH)3, Ga(OH)3 and In(OH)3:

[0034] Place 375.1 g Al(NO3)3·9H2O (or 255.7 g Ga(NO3)3·xH2O or 300.8 g In(NO3)3·xH2O) in a beaker and add water to dissolve it completely. First, add 8 M NaOH dropwise to the solution. When a white flocculent precipitate begins to form, replace the 8 M NaOH with 1 M NaOH. At the same time, monitor the pH of the solution and add NaOH until the pH of the solution reaches 7. 3+ or Ga 3+ or In 3+ Completely precipitated as Al(OH)3 or Ga(OH)3 or In(OH)3, stop adding NaOH at this time, let the precipitation stand, then pour out the upper solution, and wash the precipitate with methanol and pure water 2 to 3 times to remove the soluble impurities in the precipitate, dry the precipitate at 120°C, collect the generated solid, cool and grind to obtain 78.0g Al(OH)3 or 120.7g Ga(OH)3 or 165.8g In(OH)3.

[0035] The prepared boron hydroxides were characterized and tested, such as Figure 1 shown. Figure 1 (a) is a transmission electron microscope image of the Al(OH)3 catalyst. It can be seen from the figure that the synthesized Al(OH)3 has a regular or incompletely regular flake structure, among which the incompletely regular flake Al(OH)3 is 1.40μm long and 1.52μm wide; the regular flake structure is approximately square, with a length and width of approximately 1.68μm. Figure 1 (b) is a transmission electron microscope image of the Ga(OH)3 catalyst. It can be seen from the image that the synthesized Ga(OH)3 has a regular rod-like structure with a length of about 1.04 to 2.27 μm. Figure 1(c) in the figure is a transmission electron microscope image of the In(OH)3 catalyst. It can be seen from the figure that the synthesized In(OH)3 has a spherical structure with a diameter of about 16nm.

[0036] Figure 1 (d) in the figure is the X-ray diffraction pattern (XRD) of the Al(OH)3 catalyst. The Al(OH)3 synthesized by alkali precipitation method has sharp characteristic peaks at 29.4°, 31.4°, 38.6°, 47.8° and 48.5°, belonging to the (0-11), (-111), (-1-21), (-2 11) and (0-12) crystal planes, respectively. Figure 1 (e) in the figure is the XRD spectrum of Ga(OH)3 catalyst. The synthesized Ga(OH)3 has crystal planes such as (220), (310), (222), and (321). Figure 1 (f) in the figure is the XRD pattern of the synthesized In(OH)3 catalyst, which has obvious (200) and (400) crystal planes.

[0037] The above characterization results show that boron hydroxides Al(OH)3, Ga(OH)3 and In(OH)3 were successfully synthesized.

[0038] (2) Weigh 100 mg of PFOA solid into a 1.0 L volumetric flask, stir to dissolve and make up to volume to obtain a 100 mg / L PFOA stock solution;

[0039] (3) Place a 300W mercury lamp in an XPA-7 photoreactor and preheat for 30 minutes to ensure that it outputs a stable light intensity;

[0040] (4) 7.5 mL of 100 mg / L PFOA stock solution and 142.5 mL of deionized water were mixed to obtain a mixed solution. The pH of the mixed solution was adjusted to 7. 8 mg of boron hydroxide Al(OH)3 was added to the mixed solution. The concentration of Al(OH)3 in the mixed solution was 53.3 mg / L and the concentration of PFOA in the mixed solution was 5 mg / L. The mixture was then stirred in the dark for 2 h to reach adsorption equilibrium. 30.0 mL of the solution was placed in a quartz tube for light irradiation reaction. At the preset reaction time point, the lampshade of the photoreactor was pulled down. 1.0 mL of the reaction solution was taken out from the photoreactor tube and placed in a 10 mL plastic centrifuge tube. 4 mL of methanol was added and the mixture was stirred and extracted for 40 min. The change of PFOA concentration was monitored using a high performance liquid chromatography-mass spectrometer and the degradation rate of PFOA was calculated.

[0041] Example 2: The difference from Example 1 is that in step (3), 300 mg of boron hydroxide Ga(OH)3 is added to the mixed solution, and the concentration of Ga(OH)3 in the mixed solution is 2000.0 mg / L.

[0042] Example 3: The difference from Example 1 is that in step (3), 42 mg of boron hydroxide In(OH)3 is added to the mixed solution, and the concentration of In(OH)3 in the mixed solution is 280.0 mg / L.

[0043] Example 4: The difference from Example 1 is that in step (3), the 300W mercury lamp light source is replaced by a yellow or red LED lamp, and the XPA-7 photoreaction instrument is replaced by a homemade photoreaction device, such as Figure 2 As shown (in the figure, 1 is a quartz tube, 2 is a radiometer, 3 is a stirrer, 4 is an LED lamp, 5 is a multi-layer test tube rack for accommodating a plurality of quartz tubes, 6 is a fan for controlling the temperature, the multi-layer test tube rack is placed on the stirrer, the LED lamp and the fan are arranged around the multi-layer test tube rack, the radiometer is used to detect and record the light intensity around the quartz tube, and the method of use is: add the solution to be tested into the quartz tube, then place the quartz tube on the multi-layer test tube rack, turn on the stirrer, after sufficient mixing, turn on the LED lamp and the fan, and monitor the light intensity in the reaction through the radiometer), repeat the photocatalytic degradation experiment.

[0044] Example 5: The difference from Example 4 is that in step (3), 300 mg of boron hydroxide Ga(OH)3 is added to the mixed solution, and the concentration of Ga(OH)3 in the mixed solution is 2000.0 mg / L.

[0045] Example 6: The difference from Example 4 is that in step (3), 42 mg of boron hydroxide In(OH)3 is added to the mixed solution, and the concentration of In(OH)3 in the mixed solution is 280.0 mg / L.

[0046] Embodiment 7: The difference from Embodiment 4 is that in step (3), the yellow light is replaced by a red LED lamp.

[0047] The difference between Example 8 and Example 7 is that in step (3), 300 mg of boron hydroxide Ga(OH)3 is added to the mixed solution, and the concentration of Ga(OH)3 in the mixed solution is 2000.0 mg / L.

[0048] Example 9: The difference from Example 7 is that in step (3), 42 mg of boron hydroxide In(OH)3 is added to the mixed solution, and the concentration of In(OH)3 in the mixed solution is 280.0 mg / L.

[0049] Comparative Example 1: Photodegradation of PFOA alone

[0050] (1) Weigh 100 mg of PFOA solid into a 1 L volumetric flask and stir to dissolve to obtain a 100 mg / L PFOA stock solution;

[0051] (2) Place a 300W mercury lamp in an XPA-7 photoreactor and preheat for 30 minutes to allow it to output a stable light intensity;

[0052] (3) 7.5 mL of 100 mg / L PFOA stock solution and 142.5 mL of deionized water were mixed evenly to obtain a mixed solution. The pH of the mixed solution was adjusted to 7. The concentration of PFOA in the mixed solution was 5 mg / L. Then, a light reaction was carried out. At the preset reaction time point, the lampshade of the photoreactor was pulled down. 1.0 mL of the reaction solution was taken out from the photoreactor tube and placed in a 10 mL plastic centrifuge tube. 4 mL of methanol was added and the mixture was stirred and extracted for 40 min. The change of PFOA concentration was monitored using a high performance liquid chromatography-mass spectrometer and its degradation rate was calculated.

[0053] Comparative Example 2: The difference from Comparative Example 1 is that in step (2), the 300W mercury lamp light source is replaced by yellow light, the XPA-7 photoreactor is replaced by a homemade photoreaction device, and the photodegradation experiment is repeated.

[0054] Comparative Example 3: The difference from Comparative Example 2 is that in step (2), the yellow light is replaced by red light and the photodegradation experiment is repeated.

[0055] The degradation performance diagrams of PFOA in Examples 1 to 9 and Comparative Examples 1 to 3 are as follows: Figure 3 and Figure 4 shown.

[0056] Depend on Figure 3 It can be seen that under the optimal reaction conditions, compared with the single photodegradation system, the degradation of PFOA after adding Al(OH)3, Ga(OH)3, and In(OH)3 was promoted by 18.5%, 33.6%, and 7.1% respectively after 48h UV irradiation. There was no obvious degradation of PFOA after yellow or red LED irradiation. The photocatalytic efficiency of Al(OH)3, Ga(OH)3, and In(OH)3 on PFOA at the optimal dose can reach up to 23.5% ( Figure 4 ).

[0057] In order to determine the catalytic performance of Al(OH)3, Ga(OH)3 and In(OH)3, the degradation concentration of PFOA was evaluated with 1 mmol hydroxide (the formula is: degradation concentration (L·mmol -1 )=PFOA degradation concentration / amount of hydroxide substance). The relationship of utilization efficiency is Al(OH)3>In(OH)3>Ga(OH)3 (such as Figure 5 shown).

[0058] In the above-mentioned photocatalytic reaction system, the catalytic mechanism of boron hydroxide is as follows: on the one hand, the synthesized boron hydroxide has a positive charge on its surface under the condition of pH 7, and there is an electrostatic interaction between it and the negatively charged PFOA. PFOA is adsorbed on the hydroxide surface in a monodentate complexation manner, and there is a weak hydrogen bond between the CF2 group of PFOA and the hydroxyl group on the hydroxide surface. This complexation reduces the bond energy of the α-CC bond in PFOA. Under the action of UV light, the α-CC bond in PFOA is easily dissociated by light excitation to form C7H 15 · and CO2·; on the other hand, the holes in the hydroxide can oxidize PFOA ions; in addition, under the irradiation of yellow light and red light, the hydroxide has a two-photon absorption effect, which reduces the dissociation energy of the α-CC bond and makes the CC bond easier to break and form C7H 15 · and CO2·( Figure 6 ).

[0059] In order to confirm the mechanism of photocatalytic degradation of PFOA by hydroxide in the above embodiment, the applicant conducted the following experiment: The zero potential point of the hydroxide was measured, and the results showed that the zero potential points of the three hydroxides were 8.40, 7.09 and 7.56 respectively. Under pH = 7, the surface of the hydroxide has a positive charge ( Figure 7 ).

[0060] The original and PFOA-adsorbed hydroxides were characterized by infrared spectroscopy. According to the calculation formula Δν=ν as (COO - )-ν s (COO - ) It can be obtained that the wave number differences in PFOA-Al(OH)3, PFOA-Ga(OH)3 and PFOA-In(OH)3 systems are 261 cm -1 、271cm -1 and 277cm -1 ( Figure 8 (a)-(d)) in the figure confirms that there is a monodentate coordination complex between the hydroxide and PFOA.

[0061] 19The results of F NMR spectroscopy showed that the peaks of -84.12, -121.26, -123.88, -124.34, -124.80, 125.14 and -128.82 ppm in the PFOA sample were attributed to the terminal C(8)F3 and C(2-7)F2, respectively. After PFOA was adsorbed on the hydroxide surface, the terminal C(8)F3 groups in PFOA-Al(OH)3, PFOA-Ga(OH)3 and PFOA-In(OH)3 showed shifts of 0.42, 0.40 and 0.32 ppm, respectively. In addition, the peaks of the C(3-6)F2 group overlapped into a large peak, indicating that the CF2 group of PFOA may interact with the surface hydroxyl groups of the hydroxide through hydrogen bonds ( Fig. 9 ).

[0062] The results of EPR test, quenching experiment and aeration experiment show that the holes in the hydroxide can oxidize PFOA ions. The results of UV-visible diffuse reflectance test show that Al(OH)3 has a significant absorption peak at 300.0nm. Similarly, Ga(OH)3 and In(OH)3 have significant absorption peaks at 268.0nm and 312.0nm, respectively. Therefore, the band gap energy E of Al(OH)3, Ga(OH)3 and In(OH)3 is g 4.1eV, 4.6eV and 4.0eV respectively ( Fig.10 ). The hv range of yellow light to red light (496.0nm-775.0nm) is about 1.6eV to 2.5eV, so the range of hv to 2hv is 3.2eV to 5.0eV. The E of hydroxide g Within this range, there may be a two-photon absorption effect. Hydroxide exhibits an upconversion luminescence effect under 650nm laser excitation (emission peaks appear at 510.0nm and 460.0nm). The variable power test results show that when the excitation power increases, the luminescence intensity is proportional to the square of the power, which proves that hydroxide has a two-photon absorption effect ( Fig.11 ).

[0063] Example 10: Analysis of factors affecting PFOA degradation under photocatalytic system

[0064] From the above examples, it can be seen that Al(OH)3 has the best photocatalytic performance for PFOA degradation. In this example, the pH of the water body is adjusted to 3-7 or a certain amount of common anions (Cl - 、SO4 2- and HCO3 - 、NO3 - ) to conduct photocatalytic experiments to determine the impact of water quality factors on the photocatalytic degradation performance of Al(OH)3 for PFOA.

[0065] After 48h UV light irradiation, Al(OH)3 has a good photocatalytic effect on PFOA under non-extreme conditions (pH=3.0-7.0); Cl - 、SO4 2- and HCO3 - The degradation of PFOA was significantly inhibited by NO3. During the 48h light reaction, the degradation rates of PFOA decreased by 4.2%, 15.1% and 17.5%, respectively. - There was no significant inhibitory effect on the degradation of PFOA, which only decreased from 53.0% to 52.8%.

[0066] The above results show that boron hydroxides, especially Al(OH)3 solids, have certain application potential and can be considered for the degradation of PFOA in water.

[0067] Comparative Example 4: The difference from Example 2 is that Ga2O3 is used instead of the boron hydroxide Ga(OH)3, and the concentration used for comparison here is 0.5 g / L.

[0068] Comparative Example 5: The difference from Example 3 is that In2O3 is used instead of boron hydroxide In(OH)3, and the concentration used for comparison here is 0.5 g / L.

[0069] By comparing the degradation efficiency of PFOA in Example 2-Example 3 and Comparative Example 4-Comparative Example 5, it was found that the catalytic performance of Ga(OH)3 on PFOA was improved by about 18% compared with Ga2O3 at the same concentration, and the catalytic performance of In(OH)3 on PFOA was improved by about 12% compared with In2O3, indicating that boron hydroxides have a better degradation effect on PFOA than oxides and have broader application prospects.

Claims

1. A method for photocatalytic degradation of perfluorooctanoic acid in water using boron hydroxide, characterized in that: The steps are: adding boron hydroxide as a photocatalyst to water containing perfluorooctanoic acid, fully mixing, and then performing a photocatalytic degradation reaction under a light source.

2. The method according to claim 1, characterized in that The boron hydroxide is aluminum hydroxide, gallium hydroxide or indium hydroxide.

3. The method according to claim 2, characterized in that The mass ratio of perfluorooctanoic acid to aluminum hydroxide is 1:8-12.

4. The method according to claim 2, characterized in that: The mass ratio of perfluorooctanoic acid to gallium hydroxide is 1:300-600.

5. The method according to claim 2, characterized in that: The mass ratio of perfluorooctanoic acid to indium hydroxide is 1:40-60.

6. The method according to claim 2, characterized in that The preparation method of the boron hydroxide adopts an alkali precipitation method, and the steps are: adding a sodium hydroxide solution of a first concentration dropwise into a solution containing an aluminum salt, a gallium salt or an indium salt to generate a white flocculent precipitate, then adding a sodium hydroxide solution of a second concentration, and after the precipitate is completely generated, washing the precipitate with a solvent, drying, cooling and grinding the obtained solid, and the obtained solid powder is the boron hydroxide.

7. The method according to claim 6, characterized in that The concentration of the first concentration sodium hydroxide solution is 8-10M, and the concentration of the second concentration sodium hydroxide solution is 1-2M.

8. The method according to claim 7, characterized in that The pH range of the water containing perfluorooctanoic acid is 3-7.

9. The method according to claim 1, characterized in that: The light source is ultraviolet light, yellow light or red light.

10. The method according to claim 1, characterized in that The conditions of the degradation reaction are: reacting at 24-26° C. for 24-50 hours.

Citation Information

Patent Citations

  • Method for nano-scale gallium oxide vacuum-ultraviolet photocatalytic degradation of perfluorooctanic acid

    CN108264127A

  • In-Ga2O3 composite photocatalyst, and preparation method and application thereof

    CN111569856A

  • In2O3 photocatalyst for degrading perfluorooctanoic acid and preparation method thereof

    CN114100603A

  • Technology for preparing ozone through photocatalysis and synthesis method of photocatalyst

    CN115920874A

  • Photocatalyst composition and photocatalyst body formed thereof

    JP2005137976A